The Rural Education Research and Development Centre - David McSwan (Journal of Research in Rural Education, 1994)
The Rural Education Research and Development Centre (RERDC) is the only national centre in Australia devoted to research in rural education. Below, I describe the history, structure, activities, and future goals of the RERDC, located at James Cook University of North Queensland.